A golpe de calcetin - Hinojosa, Francisco; Barajas, Rafael (Mexico, D.F. : Fondo de Cultura Economica, 2000)
The story of a newspaper boy in Mexico City. After a friend has been injured by a thief, Manuel is instrumental in capturing the thief, and as a result gets his name in the paper.
Includes index.
"Para los que leen bien"--P. [4] of cover.
011-014.
006-009.
Keywords: Newspaper vendors -- Mexico City (Mexico) -- Juvenile fiction; Mexico City (Mexico) -- Juvenile fiction